Ladakh.: Eine landeskundliche Skizze - Nissel, Heinz (ERDKUNDE, 1977)
Ladakh, part of the state of Jammu & Kashmir, is at 95 876 km2 the largest district of the Indian Republic but contains only 105 291 inhabitants (1971). It deserves attention because of its position as an area of geopolitical tension between Asia’s four militarily strongest nations (U.S.S.R., China, India and Pakistan - Red China has occupied the N.E.,the region of Aksai Chin [37 355 km2] since1962) and is today both in its natural and cultural features the only accessible region of Tibet. The paper attempts to provide an introduction to the potentialities of the area and the uses of them made by man, thus to illustrate the latest developmental trends. Since foreign visitors were admitted to the area in 1974, a ’tourist boom’ has started, which in the near future is going to change the still static character of one of the world’s most isolated and backward regions. The development of the infrastructure forced by India for military reasons is leading to an economic improvement for the native population, but at the same time to a decline in the old cultural traditions and in the Lamaist philosophy of life.